Melatonin Treatment of Apricot Trees Leads to Maintenance of Fruit Quality Attributes during Storage at Chilling and Non-Chilling Temperatures - Jorge Medina-Santamarina; Pedro Javier Zapata; Juan Miguel Valverde; Daniel Valero; María Serrano; Fabián Guillén (Agronomy, 2021)
The effects of preharvest melatonin treatment on apricot crop yield and fruit quality properties at harvest and during storage have not yet been investigated. Apricot trees, of the ‘Colorado’ and ‘Mikado’ cultivars, were sprayed with 0.1 mM melatonin at three key points of fruit development. Fruit were harvested at commercial ripening stage and yield was higher in melatonin treated trees than in the controls. Fruit were stored at 1 and 8 °C for 21 and 28 days, respectively. Samples were taken weekly and left at 20 °C for 1 day. Weight losses, as well as reduction in firmness and acidity, were delayed in fruits from melatonin treated trees, showing an effect of treatment on delaying the postharvest ripening process, which was attributed to a reduced ethylene production in both cultivars and at both storage temperatures. In addition, chilling injury symptoms were observed in apricots stored at 1 °C, which were reduced by preharvest melatonin treatment. Moreover, apricot from melatonin-treated fruit retained higher total phenolic content than the controls after 14 days of storage, although the phenolic profile was not affected by treatment. Thus, melatonin could be a useful tool for practical purposes to improve apricot crop yield and maintain fruit quality properties during storage.